Analisis Kohesi Dan Koherensi Dalam Editorial Mediaindonesia.Com Dan Pemanfaatannya Sebagai Media Pembelajaran Video Podcast Materi Teks Editorial Kelas XII SMA - Hudawati, Retna Intendyah Siti Nur; Musa, Safuri; Rosalina, Sinta (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aims of this research are (1) to determine the use of cohesion and coherence in Mediaindonesia.com editorials; (2) use of cohesion and coherence in building editorial texts effectively; and (3) utilizing the research results as a learning medium for video podcast editorial text material for class XII high school. The data source for this research comes from an editorial at Mediaindonesia.com with the theme of fraudulent financial practices in the Ministry of Finance which was published in March 2023. Meanwhile, the objects studied are sentences and paragraphs that contain cohesive devices and meaning relationships in them. The theory that is the basis for determining cohesion comes from the opinion of M.A.K Halliday and Ruqaiya Hasan, divided into (1) grammatical cohesion: reference, conjunction, ellipsis and substitution; and (2) lexical cohesion: synonyms, antonyms, repetition, hyponymy, meronymy, and collocation. Coherence analysis is based on the theory of meaning relationships put forward by Harimurti Kridalaksana. Apart from that, the research results were developed into a video podcast utilizing theories from Vincec Fernandez, et al. Based on the results of the analysis, the overall data obtained was 365 uses of grammatical cohesion, 37 uses of lexical cohesion, and 78 meaning-coherence relationships. The use of cohesion and coherence together with an understanding of the structure and linguistic rules of editorial texts plays an important role in creating effective texts.